2021
DOI: 10.1016/j.meegid.2021.104971
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress on the mutations of SARS-CoV-2 spike protein and suggestions for prevention and controlling of the pandemic

Abstract: Severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) infection has caused a global pandemic in the past year, which poses continuing threat to human beings. To date, more than 3561 mutations in the viral spike protein were identified, including 2434 mutations that cause amino acid changes with 343 amino acids located in the viral receptor-binding domain (RBD). Among these mutations, the most representative ones are substitution mutations such as D614G, N501Y, Y453F, N439K/R, P681H, K417N/T, and E4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 120 publications
(193 reference statements)
0
17
0
Order By: Relevance
“…This mutation occurred due to the amino acid substitution and was found circulating in European countries such as the United Kingdom, Denmark, Germany, Sweden, Switzerland, France, Italy, Iceland, Luxembourg, Norway, and Poland. This mutation is also reported in Asian countries such as Singapore and the Middle East, such as UAE (180)(181)(182). This mutation is found in the RBM (receptor-binding motif) and increases the binding affinity to the ACE2 receptor.…”
Section: N439kmentioning
confidence: 81%
See 1 more Smart Citation
“…This mutation occurred due to the amino acid substitution and was found circulating in European countries such as the United Kingdom, Denmark, Germany, Sweden, Switzerland, France, Italy, Iceland, Luxembourg, Norway, and Poland. This mutation is also reported in Asian countries such as Singapore and the Middle East, such as UAE (180)(181)(182). This mutation is found in the RBM (receptor-binding motif) and increases the binding affinity to the ACE2 receptor.…”
Section: N439kmentioning
confidence: 81%
“…Therefore, it is an epidemiologically significant mutation, and researchers are focusing on this mutation for further study. It was found that this mutation neutralizes the activity of several mAbs (monoclonal antibodies) ( 180 , 181 ). The mutation may help the virus to evade immunity.…”
Section: Significant Mutations In Emerging Variants and Immune Escapementioning
confidence: 99%
“…Naqvia et al, 2020 , Bal et al, 2021 , Centers for Disease Control and Prevention. Coronovirus Disease, 2019 , Chen and Zhong, 2020 , Dai and Gao, 2020 , Denison et al, 2011 , Fitzsimmons et al, 2018 , Grubaugh et al, 2020 , Hoffmann et al, 2021 , Korber et al, 2020 , Li et al, 2021 , Leung et al, 2021 , Liu et al, 2021 , McCarthy et al, 2021 , Sanjuán and Domingo-Calap, 2016 , V’kovski et al, 2021 , Wang et al, 2020a , Wang et al, 2020b , World Health Organisation. SARS-COV-2 Variants of Concern and Variants of Interest, updated 1 July, 2021 , Wu et al, 2020b , Winger and Caspari, 2021 , Wang et al, 2021 .…”
Section: Uncited Referencesmentioning
confidence: 99%
“…Notwithstanding, viral immune escape could also be caused by epitope-associated residue substitutions, deletions and insertions that lead to an altered epitope conformation, increased receptor binding affinity and overall antigenicity [18] , [19] , [20] , [21] . The concept of immune escape [22] and mutations of SARS-CoV-2 [23] have been excellently reviewed in recent papers for readers reference.…”
Section: Spike Glycoprotein: the Molecular And Structural Similarities And Differencesmentioning
confidence: 99%